2012
DOI: 10.1002/joc.3493
|View full text |Cite
|
Sign up to set email alerts
|

Least square support vector and multi‐linear regression for statistically downscaling general circulation model outputs to catchment streamflows

Abstract: This study employed least square support vector machine regression (LS-SVM-R) and multi-linear regression (MLR) for statistically downscaling monthly general circulation model (GCM) outputs directly to monthly catchment streamflows. The scope of the study was limited to calibration and validation of the downscaling models. The methodology was demonstrated by its application to a streamflow site in the Grampian water supply system in northwestern Victoria, Australia. Probable predictors for the study were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 54 publications
1
92
0
1
Order By: Relevance
“…The correlation analysis between any two of the selected explanatory variables was executed to distinguish paired collinearity. To reduce the multicollinearity, each of the paired collinear variables was removed by turns, and the other selected explanatory variables were then individually reintroduced to the stepwise regression procedures to seek a balance between the best statistical performance of the model and minimal multicollinearity of the explanatory variables (Sachindra et al, 2013). The correlation analysis and the stepwise regression model procedures were combined in this study to obtain an optimized model with the least number of variables and best statistical performance.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation analysis between any two of the selected explanatory variables was executed to distinguish paired collinearity. To reduce the multicollinearity, each of the paired collinear variables was removed by turns, and the other selected explanatory variables were then individually reintroduced to the stepwise regression procedures to seek a balance between the best statistical performance of the model and minimal multicollinearity of the explanatory variables (Sachindra et al, 2013). The correlation analysis and the stepwise regression model procedures were combined in this study to obtain an optimized model with the least number of variables and best statistical performance.…”
Section: Model Developmentmentioning
confidence: 99%
“…Conversely, in spite of the weakness of assumption of static relationships between climate and hydrological response patterns in the future, statistical models have advantages of both high efficiency in computation and acceptable performance in modeling when applied over multiple sites. The performance of empirical models in climate change studies appears to be powerful when incorporating downscaled general circulation model (GCM) outputs (Sachindra et al, 2013;Li et al, 2016). For example, Li et al (2016) used log-linear models for 21 rainfall stations and 7 hydrometric stations to predict hydrological drought.…”
mentioning
confidence: 99%
“…Anandhi et al (2008) used LS-SVM to downscale monthly precipitation to the river basin scale in India and found that the LS-SVM model was a feasible choice for obtaining future precipitation projections at a river basin scale, but that it was unable to mimic observed extreme precipitation events. More recently, LS-SVM has been widely used in regression-based downscaling methods (Raje and Mujumdar 2011;Sachindra et al 2013).…”
Section: ) Ls-svmmentioning
confidence: 99%
“…The approach consists of least squares and biharmonic spline surface. The technique of least squares has been widely used in many fields: statistics [14], image processing [15] and physics [16,17], and so on [18]. Biharmonic spline surface has been used in some fields, such as marine satellite measurement data [19], integration of logging and seismic data [20], image deformation [21], to name a few [22].…”
Section: Introductionmentioning
confidence: 99%